Usulan Pengembangan Produk Backpack Standard dengan Menggunakan Metode Quality Function Deployment (QFD) - Muhammad Gufie Trio Nanda; Puti Renosori (UNISBA Press, 2021)
Abstract. Carion Bags Industri is a company engaged in the bag industry. Carion Bags Industri produces standard backpacks, waist bags, and traveling bags. The standard backpack product designs that are marketed today still do not meet the wishes of their users so that it will affect the company's profits. The objectives of the research are a). Identify standard backpack products like what consumers want; b) Designing standard backpack products in accordance with consumer specifications; c) Designing a standard backpack product that is multifunctional according to the wishes of consumers. The Quality Function Deployment (QFD) method is carried out by distributing open questionnaires, external closed questionnaires, validity tests, reliability tests, distributing actual questionnaires, data adequacy tests, phase 1, phase 2, phase 3. The results of the study are a). Product identification has 12 variables, namely low prices, available laptop storage pockets, handphone charge features, attractive designs, strong to withstand heavy loads, durable (durable), waterproof, resilient, easy to find in various stores, warranty, comfortable to use and lightweight materials ; b) Standard backpack product specifications with a size of 45cm x 30cm x 18 cm, 25 liters of load, laptop storage bag, rectangular shape, there is a cellphone charge panel, the inside is made of polyfoam foam and the outside is made of cordura; c) Multifunctional standard backpack products, namely laptop storage pockets, handphone charge panels, durable, waterproof, available in stores and via online, strong to withstand heavy loads, guaranteed, comfortable to use, made of light weight and attractive color designs. Abstrak. Carion Bags Industri merupakan perusahaan yang bergerak dibidang industri tas. Carion Bags Industri memproduksi produk backpack standard, waist bag, dan traveling bag. Desain produk backpack standard yang dipasarkan sekarang masih belum memenuhi keinginan penggunanya sehingga akan mempengaruhi keuntungan perusahaan. Tujuan dari penelitian adalah a). Mengidentifikasi produk backpack standard seperti apa yang diinginkan konsumen; b) Merancang produk backpack standard yang sesuai dengan spesifikasi konsumen; c) Merancang produk backpack standard yang multifungsi sesuai dengan keinginan konsumen. Metode Quality Function Deployment (QFD) dilakukan dengan penyebaran kuesioner terbuka, kuesioner tertutup eksternal, uji validitas, uji reliabilitas, penyebaran kuesioner sebenarnya, uji kecukupan data, fasa 1, fasa 2, fasa 3. Hasil dari penelitian adalah a). Identifikasi produk terdapat 12 variabel yaitu harga murah, tersedia kantong penyimpanan laptop, fitur charge handphone, desain menarik, kuat menahan beban berat, tahan lama (awet), tahan air, tahan banting, mudah ditemukan diberbagai toko, garansi, nyaman digunakan dan bahan ringan; b) Spesifikasi produk backpack standard dengan ukuran 45cm x 30cm x 18 cm, bermuatan 25 liter, kantong penyimpanan laptop, bentuk persegi panjang, terdapat panel charge handphone, bagian dalam berbahan busa polyfoam dan bagian luar berbahan cordura; c) Multifungsi produk backpack standard yaitu tersedia kantong penyimpanan laptop, terdapat panel charge handphone, tahan banting, tahan air, tersedia ditoko dan via online, kuat menahan beban berat, bergaransi, nyaman digunakan, berbahan ringan dan memiliki desain warna yang menarik.